The The role of work engagement and work meaningfulness on turnover of nurses in Rundu, Namibia (Namibian Journal for Research, Science and Technology, 2022)
Turnover, in the nursing profession seems to be problematic and this jeopardized the mandate of delivering safe and effective care. The nursing sector has one of the highest in employee turnover around the world. Looking into work engagement and work meaningfulness can be used as mitigating factors which organisations can consider to curb turnover. In the Namibian context literature on nurses’ engagement and work meaningfulness is inadequate. A cross-sectional survey design was used. A total of n=168 nurses from Rundu hospitals and clinics, participated in the study. Findings revealed that there is no statistically significant relationship between turnover and work-engagement (r=0.095; p=0.222) of nurses in Rundu, Namibia. Findings also revealed that there is no statistically significant relationship between turnover and work-meaningfulness (r=-0.003; p=0.966) of nurses in Rundu, Namibia. A positive and statistically significant relationship between work-engagement and work-meaningfulness (r=0.587**; p=
Keywords: Turnover; employee engagement; work meaningfulness; nurses; Namibia